(3eNJUQ cJGH GdCQKeGWjbjs - (3eLghds
(3ChdgG (B:s
(3jSe Gddg bUOfG Cf fUd HeG bOefGg ef GdYdhe GdJYGdjejI Gdaf GdeYQha HGdCQKjeGWjbj heG LQJ GdYGOI HEjQGOg ajg hYdi GdhLg GdPj LQJ Hg Ydi Cf cGf s
(3BNQgG (B:s
(3hbO JQcfG CMhGdG CYjO PcQgG aj gPG GdehVY NGQLI Yf bGfhf GdUfGYI hbO Hbj ef Yde GdMSGH eG jYfj aj GdGSJYeGd hGdGSJNQGL hgh eYO fMh eG Je GdcJGHs
(3JHUQI GdeDda (B:s
(3efShH dGHf SjfGs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdQjGVjGJs